Management and Follow-Up of Complicated Crown Fractures with Intrusive Luxation of Maxillary Incisors in an 8-Year-Old Boy - Niusha Abazarian; Shabnam Milani; Moahammad Hassan Hamrah; Marzieh Salehi Shahrabi (Case Reports in Dentistry)
Intrusive luxation is a severe form of dental injury which causes damage to the pulp and supporting structures of a tooth because of its dislocation into the alveolar process. This paper shows the case of the reeruption of maxillary incisors accompanied by complicated crown fractures after 3 months. An 8-year-old boy patient was referred to the Department of Pedodontic Dentistry of Tehran University of Medical Science, Tehran, Iran, 18 hours after a fall at school. Clinical and radiographic examinations revealed intrusive luxation of both incisors with complicated crown fractures. Cervical pulpotomy is the treatment of choice for traumatized immature intruded teeth with pulp exposure. Two months later, the right central incisor teeth reerupted to a normal position and the final aesthetic restorations were done. The left central incisor was spontaneously repositioned with external root resorption, and the team decided to use interim medication (calcium hydroxide) in the root canal for stopping the process of resorption, and by the 9-month follow-up, the process of resorption had been stopped. An MTA plug was placed into the canal, and the final esthetic restorations were done.